Changes in thermal preference, respiratory and metabolic patterns in Tropidurus torquatus: Population responses from two distinct Brazilian biomes - Matos, Sofia L B da S [UNESP]; de Souza Porto, Lays [UNESP]; Bars-Closel, Melissa [UNESP]; de Barros, Fábio Cury; Kohlsdorf, Tiana; Bícego, Kenia C [UNESP]; Gargaglioni, Luciane H [UNESP] (Elsevier, 2025)
Variations in structural and climatic conditions of habitats, particularly in environmental temperatures, emerge as a pivotal determinant exerting broad influence on physiological processes, such as modifications in ventilation and metabolism within certain species. We investigated the thermal preference, ventilatory, and metabolic responses to acclimation in two Brazilian populations of the lizard Tropidurus torquatus - one population from the Pampa biome and the other from the restinga (sandbank) ecosystems in the Atlantic Forest biome. We divided lizards into three distinct acclimation temperatures (20 °C - 'cold', 25 °C - 'warm', and 30 °C - 'hot' regimes) and, after three weeks, recorded their preferred temperatures. Subsequently, we measured ventilation and metabolism in the same individuals at 20 °C, 25 °C, and 30 °C. Both populations exhibited similar responses to acclimation in thermal variables. However, in the extreme acclimation regimes, the Pampa population selects colder temperatures more frequently than the Restinga population. We did not detect any effect of acclimation or population on ventilation. In contrast, we identified changes in respiratory frequency likely related to changes in acclimation temperature regimes for both populations. In terms of metabolism, we recorded lower oxygen consumption in the Pampa population at warm and hot acclimation regimes. Our findings suggest that physiological responses to acclimation in T. torquatus may be intricately molded by the specific environmental contexts in which populations are situated. Animals originating from the southern population exhibit increased thermal responses - like the reduction of O2 consumption when faced with 30 °C experimental temperature - potentially attributed to their exposure to more variable temperature regimes in their native habitat.